Cirrhotic cardiomyopathy: Implications for liver transplantation. Issue 6 (26th May 2017) - Liu, Hongqun; Jayakumar, Saumya; Traboulsi, Mouhieddin; Lee, Samuel S.
Abstract : The majority of patients on a waiting list for liver transplantation have end‐stage liver disease. Because of the marked peripheral vasodilatation of end‐stage cirrhosis that masks a latent myocardial dysfunction, cardiac abnormalities in the resting state are usually subclinical and escape the attention of physicians. However, when challenged, the systolic and diastolic contractile responses are attenuated. In addition to these contractile abnormalities, morphological changes, such as enlargement or hypertrophy of cardiac chambers, and electrophysiological repolarization changes, including a prolonged QT interval, can be observed. The constellation of these cardiac abnormalities is termed cirrhotic cardiomyopathy. Liver transplantation induces significant cardiovascular stress. Clamping of the inferior vena cava and portal vein, hemorrhage and blood/volume infusion, and ischemia/reperfusion all cause hemodynamic fluctuation. The changing cardiac preload and afterload status increases the cardiac workload, and thus, the previously subclinical ventricular dysfunction may manifest as overt heart failure during the operative and perioperative periods. Cardiac dysfunction contributes to morbidity and mortality associated with liver transplantation. Cardiovascular events are the third leading cause of death in liver recipients. However, because liver transplantation is the only definitive treatment for end‐stage liver failure and also appears to reverse cardiac abnormalities, it is important to understand the challenges of the heart in liver transplantation. This review focuses on cardiac status before, during, and after liver transplantation. Liver Transplantation 23 826–835 2017 AASLD .